2021
DOI: 10.9734/jpri/2021/v33i1831313
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Antibiotic Use and Factors Associated With Self-medication among University Students in Malaysia

Abstract: Self-medication with antibiotics is a global menace especially in developing countries due to lack of knowledge, poor access to the proper health care, and the weakness in the government’s role in monitoring and controlling the use of antibiotics. Thus, this study was carried out to identify the prevalence of antibiotic use during self-medication and the associated factors with self-medication among the students of Lincoln University College Malaysia. A quantitative research approach (i.e. cross-sectional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The risks associated with such practices include the development of antibiotic resistance, making infections more di cult to treat. Therefore, stricter regulations and public education about the dangers of self-medication are imperative [23,24]. Ensuring that antibiotics are available only through a prescription can reduce misuse.…”
Section: Discussionmentioning
confidence: 99%
“…The risks associated with such practices include the development of antibiotic resistance, making infections more di cult to treat. Therefore, stricter regulations and public education about the dangers of self-medication are imperative [23,24]. Ensuring that antibiotics are available only through a prescription can reduce misuse.…”
Section: Discussionmentioning
confidence: 99%
“…11 However, a study in Malaysia reported a low rate of self-medicated antibiotic use among university students. 12 In Indonesia, a report published by Indonesian Central Statistic Agency showed that the prevalence of selfmedication reached 84.23% in Indonesian society. 13 There is no report on specific statistics of selfmedication among university students, but several previous studies reported varying prevalence of selfmedication in several universities in Indonesia.…”
Section: Introductionmentioning
confidence: 99%